Inducing ferroptosis by traditional medicines: a novel approach to reverse chemoresistance in lung cancer - Wang, Yumin; Hu, Jing; Fleishman, Joshua S.; Li, Yulin; Ren, Zhao; Wang, Jinhua; Feng, Yukuan; Chen, Jichao; Wang, Hongquan (Frontiers in Pharmacology, 2024)
Lung cancer is the leading cause of global cancer-related deaths. Platinum-based chemotherapy is first-line treatment for the most common type of lung cancer, non-small-cell lung cancer (NSCLC), but its therapeutic efficiency is limited by chemotherapeutic resistance. Therefore, it is vital to develop effective therapeutic modalities which bypass the common molecular mechanisms associated with chemotherapeutic resistance. Ferroptosis is a form of non-apoptotic regulated cell death characterized by iron-dependent lipid peroxidation (LPO). Ferroptosis is crucial for the proper therapeutic efficacy of lung-cancer associated chemotherapies. If targeted as a novel mechanism therapeutic, ferroptosis-modulators presents new opportunities in increasing the therapeutic efficacy of lung cancer chemotherapy. Emerging studies have revealed that pharmacological induction of ferroptosis using natural compounds boosts the efficacy of chemotherapy in lung cancer or in drug-resistant cancer. In this review we first discuss chemotherapeutic resistance (or chemoresistance) in lung cancer and briefly introduce the core mechanisms behind ferroptosis. Then, we comprehensively summarize the small-molecule compounds sourced from traditional medicines that may boost the anti-tumor activity of current chemotherapeutic agents and overcome chemotherapeutic resistance in NSCLC. Cumulatively, we suggest that traditional medicines with ferroptosis-related anticancer activity could serve as a starting point to overcome chemotherapeutic resistance in NSCLC by inducing ferroptosis, highlighting new potential therapeutic regimens used to overcome chemoresistance in NSCLC.